2019
DOI: 10.1101/783803
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting the PI3K/AKT pathway overcomes enzalutamide resistance by inhibiting induction of the glucocorticoid receptor

Abstract: ABSTRACTThe PI3K-AKT pathway has pleiotropic effects, and its inhibition has long been of interest in the management of prostate cancer, where a compensatory increase in PI3K signaling has been reported following Androgen Receptor (AR) blockade. Prostate cancer cells can also bypass AR blockade through induction of other hormone receptors, in particular the glucocorticoid receptor (GR). Here we demonstrate that AKT inhibition significantly decreases cell proliferation through b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Further, PI3K / Akt inhibition, which will downregulate de novo fatty acid synthesis, has been shown to deplete the H3K27ac epigenetic modification, thereby remodeling the chromatin landscape. This epigenetic remodeling can hinder the emergence of resistance to androgen receptor inhibition (65). Previous studies have proposed that epigenetic changes in response to metabolic stress induced by environmental changes can increase transcriptional variability in cells.…”
Section: Discussionmentioning
confidence: 99%
“…Further, PI3K / Akt inhibition, which will downregulate de novo fatty acid synthesis, has been shown to deplete the H3K27ac epigenetic modification, thereby remodeling the chromatin landscape. This epigenetic remodeling can hinder the emergence of resistance to androgen receptor inhibition (65). Previous studies have proposed that epigenetic changes in response to metabolic stress induced by environmental changes can increase transcriptional variability in cells.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the MAPK signaling pathway and the PI3K-AKT axis facilitates prostate cancer growth, migration, and invasion [145,146], while inhibition of this pathway and axis showed the opposite effects [147,148]. Activation of the PI3K-AKT axis is involved in the chemoresistance of prostate cancer [149,150]. Another study identified five differentially expressed miRNAs in the serum exosomes of prostate cancer patients, including hsa-let-7a-5p, hsa-miR-141-3p, hsa-miR-145-5p, hsa-miR-21-5p and hsa-miR-99b-5p [90].…”
Section: Prostate Cancermentioning
confidence: 99%
“…Thus, a more viable option to treat TNBC or GR-induced ENZ-resistant PCa would be to inhibit the action of the GR through other signaling pathways, while retaining the beneficial systemic effect of glucocorticoids. In ENZ-resistant PCa, these kinds of pathways could be BET ( Shah et al 2017 ) or PI3K/AKT ( Adelaiye-Ogala et al 2020 ), whereas in TNBC, STAT3 ( Conway et al 2020 ) or p38 MAPK ( Perez Kerkvliet et al 2020 ) could be targeted. Future investigations will determine if sufficient attenuation of GR signaling can be obtained through these pathways or if other yet to be discovered pathways will be more effective.…”
Section: Differential Role Of the Gr In The Steroid Receptor Crosstalk In Breast And Prostate Cancersmentioning
confidence: 99%